RE-EVACUATION OF AGRICULTURALISTS FROM WESTERN SIBERIA TO LIBERATED AREAS (1943 – 1945) - L. I. Snegireva (Вестник Кемеровского государственного университета, 2015)
The research focuses on the re-evacuation of agriculturalists from Western Siberian caused by the necessity of the restoration of agricultural industry in the country’s areas liberated from the enemy’s occupation. So the strengthening of the country’s economical and military power was dependent on this to a significant extent. The objective of the paper is to elicit the state of the human resources, the mechanisms of the performing the activity in its main directions, its extent and results. The research performed in accordance with the basic principles of historical science. The paper allows us to see that the work was preceded by great preparative efforts of the centre and locally. The attention of the authorities was focused on the issues of specialists’ re-evacuation. We accentuated the tensity of the tasks, the hardness of their implementation, their disadvantages and results. The author concludes that despite all the difficulties the tasks of specialists re-evacuation were fulfilled, but it led to serious consequences for the social and economic development of the region.